Social interaction matters to job search over the long haul - Ferreira, A. I.; Rodrigues, R.; Carvalho, H.; Truxillo, D. (Current Psychology, 2023)
Based on social cognitive, reasoned action, and basic needs theories, this study examines whether co-rumination with others about the job search mediates the positive relation between state negative affect and job search intentions. In addition, we looked at how this positive indirect effect interacts with the social support received from different sources (such as friends, family, and significant others) at the beginning and six months after the initial job search process. Using a sample of 87 graduates (job seekers) from a Portuguese masters program, we used multilevel modeling to test this moderated mediation. Ages ranged from 22 to 53 years old (M = 29.45; SD = 7.60). Data were collected using measures to assess negative affect, co-rumination, perceived social support, and job search intentions. We found an indirect effect of state negative affect on job search intentions; when job seekers perceive higher levels of social support from significant others at the beginning of the job search, the positive, mediating role of co-rumination in this relationship is increased. Further, for a sub-sample of six-month job seekers, this positive indirect effect increased when there was also an increased perception of social support from family. Discussion focuses on implications for theory and practice and the role of co-rumination for unemployed people during job search.